Natureza e Sociedade: esboços para uma antropologia em Rousseau - SILVA, Antonio Carlos Borges da (2019)
According to the philosopher Jean-Jacques Rousseau, anthropological knowledge must base the reflection on the reality of man, especially with regard to its social, political, moral, legal, pedagogical, aesthetic and religious aspects. Rousseau refuted some of the major anthropological assumptions of the eighteenth-century Enlightenment, such as universalism and rationalism, which regarded man as an abstract and rational being, contributing to the development of new theoretical fields for the sciences of man. Rousseau sustained the oneness of human nature, yet he recognized that man can be modified by historical and geographical circumstances. Human nature can thus be apprehended in its ontological and historical existence. Therefore, the analysis of the natural man, as opposed to the social man, allows us to affirm that the human phenomenon is understood in this dichotomous perspective. In entering the universe of culture, which was constituted as a kind of second nature, man changed himself, transmuting his primitive or original nature. He passed from the condition of animality to the condition of humanity. This perspective opens space for important reflections on man from the point of view of a philosophical and empirical anthropology. It may be further argued that for Rousseau there is an intrinsic relationship between historical progress, the product of civilization, and the corruption of human nature. By surrendering to historical becoming, man has built the mechanisms by which he has lost his freedom and has become a slave to social appearances, which are the simulacrum of nature. This condition was predominant as result of the establishment of civil society, labor and private property, mediated by language. Rousseau's conceptions of man as an historical being, endowed with freedom and perfectibility, have become one of the greatest legacies of modern thought in the human sciences. Thus, the present study aims to contribute to the discussions about Rousseau's thought through some anthropological sketches, considering the postulate analysis of the state of nature formulated by the author.